2019
DOI: 10.3390/agronomy9090482
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulant Application Enhances Fruit Setting in Eggplant—An Insight into the Biology of Flowering

Abstract: Eggplant (Solanum melongena L.) is a warm climate crop. Its cultivation extends to temperate regions where low temperatures can affect the course of the generative phase, which is primarily sensitive to abiotic stress. The novelty of the present investigation consisted of characterising the heterostyly, pollination, and fertilisation biology of eggplants in field cultivations, which provided a basis for explaining the effect of a protective biostimulant on these processes. We aimed to investigate the flowering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…This stimulatory response would explain the increase in flowers in the heat stressed plants. Although promoted flowering has previously attributed to other commercial ANE biostimulants (Abubakar et al, 2012;Pohl et al, 2019), there was only a significant increase in flower number in tomato plants treated with PSI-494. These results highlight that despite the ANE biostimulants being manufactured from the same raw material their processing conditions can affect their ability to provide phenotypic and physiological benefits.…”
Section: Impact Of Anes On Phenotypic and Physiological Markers Of Hementioning
confidence: 80%
See 1 more Smart Citation
“…This stimulatory response would explain the increase in flowers in the heat stressed plants. Although promoted flowering has previously attributed to other commercial ANE biostimulants (Abubakar et al, 2012;Pohl et al, 2019), there was only a significant increase in flower number in tomato plants treated with PSI-494. These results highlight that despite the ANE biostimulants being manufactured from the same raw material their processing conditions can affect their ability to provide phenotypic and physiological benefits.…”
Section: Impact Of Anes On Phenotypic and Physiological Markers Of Hementioning
confidence: 80%
“…Plants treated with C129 and PSI-494 had higher pollen viability percentages than the untreated group after heat stress exposure, without significant differences in the efficacy of both ANE biostimulants. Although previous studies have highlighted the positive impact of seaweed extracts on different pollination parameters of high value crops such as grape or eggplant (Sabir, 2015;Pohl et al, 2019), no research to date has demonstrated the protective effect of ANEs on pollen under heat stress conditions. Furthermore, it has been previously described in different plant species that different stress types can stimulate precocious flowering and further seed production as an emergency response to highly unfavorable environmental conditions (Takeno, 2016).…”
Section: Impact Of Anes On Phenotypic and Physiological Markers Of Hementioning
confidence: 99%
“…Poulton et al (2002) demonstrated that AMF colonization can enhance host plant fitness by positively affecting its reproductive functions. In addition, SEs may improve flower yield and fruit production by behaving as chelators (Battacharyya et al, 2015;Yuvaraj and Gayathri, 2017;Pohl et al, 2019). Also, hormonal responses are mainly attributed to the cytokinins present in the SE or to their production, transport, and mobilization into developing tissues, either vegetative or floral (Ganesan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the application of A. nodosum-based biostimulants has been observed to lead to changes in the expression of cherry cell-wall and cuticular wax genes (PaEXP1, Pa -Gal and PaWS), which can be correlated to a reduction in fruit cracking [145]. New research regarding effects on flowering and fruit setting in eggplant also opened up a possible new function for these biostimulants, as these characteristics were positively influenced with the application of this SWE [146].…”
Section: Ascophyllum Nodosummentioning
confidence: 99%